Design, user experience, and usability. novel user experiences : 5th International Conference, DUXU 2016, held as part of HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings /: novel user experiences : 5th International Conference, DUXU 2016, held as part of HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings. Part III : (2016) - Unknown
No abstract available